The future of Same-sex marriage in India – An analysis with other countries - Seethal Kuttappan; Dalliandeep Kaur Tiwana (Social Sciences and Humanities Open)
A marriage is considered to be holy, whether sacrament or contract. Same-sex marriage is the practice of marriage among two men or two women. There has been both strong support and conflict on communal, political, and religious grounds for same-sex marriages. Some jurisdictions through laws either allow same-sex marriages or recognize same-sex civil unions whereas others prescribe punishments for homosexual relationships. Given the lack of globally uniform approaches, there are strong possibilities for conflict and legal contradictions. This study explores the legal status of weddings between people of the same gender in India with the primary aim of examining the judicial decisions and the contribution of the Supreme Court in landmark cases related to same-sex marriages.The Supriyo Chakraborty v. Union of India connected cases (2023) are a collection of significant cases that the Supreme Court of India heard. These cases were brought up to consider the extension of marriage and family rights to individuals belonging to sexual and gender minority groups in India, where same-sex weddings or civil unions are considered illegal. The Supreme Court's rejection to recognize same-sex marriages in this case severely affected the rights of the LGBTQ community in India.This study shall also dwell on the recent developments, particularly regarding the question of marital rights vis-a-vis the case before the judiciary and what could probably be the future course of action in India. In this study, the researcher chooses a hermeneutic research method focusing on the interpretation of statutes and analyzing same-sex marriage rights of different countries with that of India.